2020
DOI: 10.1111/os.12692
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Lysosome‐Associated Protein Transmembrane‐4 as a Novel Therapeutic Target for Osteosarcoma Treatment

Abstract: Objective The aim of the study is to evaluate the expression of lysosome‐associated protein transmembrane‐4 (LAPTM4B) in human osteosarcoma tissue samples collected in our hospital, and to explore the possible correlations between the clinical pathological features of osteosarcoma patients and LAPTM4B expression. Methods Immunohistochemical (IHC) assays were performed to detect the expression levels of LAPTM4B in 62 tissue samples of osteosarcoma tissues and corresponding non‐tumor tissues. According to LAPTM4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In addition to KIF11, other members of the KIF family could affect the progression and development of cancer; most of them could be potential cancer molecular targets [ 20 ]. A previous study indicated that KIF14 could contribute to the growth of hepatocellular carcinoma (HCC) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to KIF11, other members of the KIF family could affect the progression and development of cancer; most of them could be potential cancer molecular targets [ 20 ]. A previous study indicated that KIF14 could contribute to the growth of hepatocellular carcinoma (HCC) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative PCR Assay. This experiment was performed according to the previous study [20]. The TRIzol reagent (15596026, Invitrogen, Carlsbad, CA, USA) was used to extract total RNA.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we identified that LAPTM4B promotes integrin beta1 recycling and focal adhesion dynamics, critical progress promoting skin cancer development [ 24 ]. However, LAPTM4B has not been well investigated in OS hitherto, albeit two pilot studies suggest the high expression of LAPTM4B in OS [ 25 , 26 ]. The detailed mechanism underpinning LAPTM4B dysregulation in OS is not recognized, besides, the functional phenotype and relevant mechanisms remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3d has the same images used in Figure 3d by Wang et al [3]. , figure 3b in Wang et al [4]. , and figure 3d by Chen & Zhong [5].…”
mentioning
confidence: 99%